Butyric acid production from lignocellulosic biomass hydrolysates by engineered Clostridium tyrobutyricum overexpressing Class I heat shock protein GroESL. (February 2018) - Suo, Yukai; Fu, Hongxin; Ren, Mengmeng; Yang, Xitong; Liao, Zhengping; Wang, Jufang
Highlights: Phenolic compounds and furan derivatives inhibited the growth of C. tyrobutyricum . Overexpression of groESL in C. tyrobutyricum enhanced its tolerance to inhibitors. 30 g/L butyrate at a productivity of 0.31 g/L·h and yield of 0.37 g/g was obtained. This provides an effective strategy for enhanced biomass hydrolysates utilization. Abstract: Lignocellulosic biomass is the most abundant and renewable substrate for biological fermentation, but the inhibitors present in the lignocellulosic hydrolysates could severely inhibit the cell growth and productivity of industrial strains. This study confirmed that overexpressing of native groESL in Clostridium tyrobutyricum could significantly improve its tolerance to lignocellulosic hydrolysate-derived inhibitors, especially for phenolic compounds. Consequently, ATCC 25755/ groESL showed a better performance in butyric acid fermentation with hydrolysates of corn cob, corn straw, rice straw, wheat straw, soybean hull and soybean straw, respectively. When corn straw and rice straw hydrolysates, which showed strong toxicity to C. tyrobutyricum, were used as the substrates, 29.6 g/L and 30.1 g/L butyric acid were obtained in batch fermentation, increased by 26.5% and 19.4% as compared with the wild-type strain, respectively. And more importantly, the butyric acid productivity reached 0.31 g/L·h (vs. 0.20–0.21 g/L·h for the wild-type strain) due to the shortened lag phase.